What shapes food value chains? Lessons from aquaculture in Asia - Jespersen, K.S.; Kelling, I.; Ponte, S.; Kruijssen, Froukje (Elsevier, 2014)
In this article, we explain what shapes food value chains through the analysis of selected aquaculture industries in four key Asian producing countries. Worldwide production of aquatic resources has grown rapidly in the past few decades, and aquaculture production in Asia has played a decisive role in this growth. We examine the main forms of coordination found along these value chains and the role that institutional frameworks play in governing them. We observe that negative publicity, driven by NGO and media campaigns, has led to increased use of third-party certification and the adoption of public and private standards. We find that the most sophisticated aquaculture operations in Asia are found in value chains led by retailers and branded processors and where the quality of domestic institutional frameworks has facilitated compliance with increasing demands from buyers overseas. Finally, we reflect on the sustainability challenges of aquaculture and provide four broad observations on the governance of food value chains.